Implementasi Kurikulum 2013 pada Sekolah Menengah Pertama di Kota Tangerang Selatan - Alinurdin Alinurdin; Imam Fitri Rahmadi (Jurnal Pendidikan Kewarganegaraan, 2018)
This study aims at reviewing the implementation of Kurikulum 2013 at the junior high school in South Tangerang City during the school year of 2017/2018, by looking at the components; 1) completeness of curriculum documents; 2) the quality of student books; 3) the quality of the teacher books; 4) the quality of teacher training; 5) the quality of teacher assistance; 6) teacher competencies; and 7) implementation of learning. The method that used in this study is a survey. The results of the study found that the implementation of Kurikulum 2013 in junior high schools in South Tangerang City during the school year of 2017/2018 can be said to have been done well. However, attention needs to be addressed and improvements need to be made regarding the implementation of learning, the quality of training, and the competence of teachers because they get a fairly low score.